Formalism of Authority and Agrarian Justice: Medan–Binjai Toll Road Land Dispute Analysis - Amalia Hutabarat, Feby; Utama, Yos Johan; Silviana, Ana (Jurnal Cakrawala Hukum, 2026)
This article examines whether the formalism of absolute jurisdiction in Decision Number 226/Pdt.G/2024/PN Mdn has produced agrarian justice or instead delayed the examination of the substantive rights of communities claiming to control and cultivate land affected by land acquisition for the Medan–Binjai Toll Road project. The study aims to analyze the juridical position of physical possession and land cultivation without strong formal title in the Indonesian agrarian law framework, to reconstruct the judge’s legal reasoning in classifying the dispute as an administrative action dispute, and to assess the decision from the perspective of agrarian social justice and progressive law. This research is normative legal research with a prescriptive and evaluative character, using statutory, conceptual, case, and philosophical approaches. The study finds that the court’s reasoning was procedurally valid in declaring lack of jurisdiction based on the doctrine of onrechtmatige overheidsdaad and PERMA Number 2 of 2019. However, the decision did not reach the substantive examination of whether the plaintiffs’ factual control and cultivation of the land had juridical relevance in the land acquisition regime. The article concludes that the decision was procedurally correct but substantively incomplete, because it resolved the forum issue without adequately addressing the agrarian conflict at the core of the dispute.